Un Anno Dopo: I Media Nel "Presente Continuo" Della Pandemia - Spalletta, Marica (Rivista di scienze dell'educazione, 2022)
Over the last two years, and especially starting from the beginning of the pandemic - which has in/affected our society to the point that today we are forced to distinguish between a "before and after" the Covid-19 - several and deepened analysis have focused on the role played by the media. One year later the publication of Pandemie mediali, the paper aims to question again about the Covid-19 effects on the media system, as well as on the ways in which media have stood out as powerful remedies against the spread of the social and cultural disease which has blended the spread of the health emergency.